Determinants of Fishermen and Fish Farmers Exchange Rate: A Panel Data Regression Approach - Vitri Aprilla Handayani; Sabarinsyah Sabarinsyah; Adamsyam Arrafi; Hery Sunarsono; Andini Setyo Anggraeni (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
This study examines the impact of key economic variables on the exchange rate of fishermen and fish farmers using monthly panel data by subsector/province for the period 2022-2024 sourced from BPS. The price index received by farmers (Y) is explicitly defined as the dependent variable. A panel data regression model was employed using three independent variables: Farmers' Paid Price Index ( ), the Fishermen and Fish Farmers Exchange Rate ( ), and the Fishermen's Business Exchange Rate ( ). The results showed that both and had a significant positive effect (α < 0.05) on Y, with exhibiting a stronger influence than . These findings suggest that policies aimed at controlling input prices and stabilizing exchange rates can effectively improve the welfare of fishermen and fish farmers. Furthermore, the regression model developed in this study provides a practical analytical framework for supporting data-driven policy decisions related to price dynamics and welfare enhancement in the fisheries sector.